Clinical Outcome of Urolithiasis Managed with Medorrhinum: A Case Report - Dr. Hiral K. Trivedi; Dr. Jignesh Patel (The Bioscan, 2025)
Urolithiasis is a frequently encountered clinical problem affecting both the sexes of various age groups and even children. Its prevalence is increasing globally. The treatment for kidney stones usually depends on their size, site and composition. This case report explores the potential of homoeopathy in the treatment of urinary calculus. A patient of urolithiasis reported in a clinical setting. Detailed case taking of the patient was done and individualized homoeopathic medicine was prescribed on the basis of totality of symptoms after repertorization done by Homoeopathic Medical Repertory by Dr. Robin Murphy. Medorrhinum was prescribed as the individualized medicine. The clinical status of the patient was analyzed by ultrasonography imaging. Constitutional approach of yielded encouraging results. There was symptomatic relief of the patient and post-treatment ultrasonography showed no calculus after homoeopathic interventions. Individualized medicine, Medorrhinum found effective in speedy removal of the calculus. Medorrhinum, prescribed in this case, has limited documentation in the homoeopathic literature regarding its clinical utility in urolithiasis, yet, this constitutional medicine acted favourably in alleviating the morbidity. KEYWORDS Urolithiasis, Homoeopathy, Individualized medicines, Medorrhinum, Urolithiasis Symptoms Score (USS) Scale.